PROGRAMMING RDB SOFTWARE - Xo’jayev Fayzullaxo’ja (Journals Park Publishing, 2024)
This article provides a comprehensive description of RDB (Computer digital control) programming, which is important in modern manufacturing. RDB programming ensures accuracy, consistency and efficiency in managing software, stations, milling, routers and grinders. This article explains the basic concepts of RDB programming, including the use of G-codes and M-codes for bench-top control, bench and work coordinates, and interpolation methods. The article provides information about common G-codes and M-codes, from design to execution, a simple example of the RDB programming process and the RDB program. The best practices for RDB programming will be discussed, such as double checking of coordinates, performing simulations, tool management, and document storage. The article also presents future trends in RDB programming, including automation, advanced materials, additional production and the integration of IoT and Industry 4.0 technologies. This article is a valuable resource for understanding the subtleties of RDB programming and understanding its important role in modern manufacturing.
Keywords: RDB programming, computer digital control, g-codes, m-codes, machine coordinates, work coordinates, interpolation, milling, simulation, tool management, automation. Modern manufacturing, iot and industry 4.0, additional production, advanced materials.